Design of Composite Skin Panels with Solar Panels on the Roof - Shkirenko, Serhiy; Muravlov, Volodymyr; Zyma, Oleksandr (International Journal of Engineering and Technology, 2018)
An example of typical two-sided composite (timber and plywood) skin panel design to be used as a roof member with solar panels.Â